Awareness, Utilization and Health Outcomes of National Essential Public Health Service Among Migrants in China - Xu, Xinpeng; Zhang, Qinglong; You, Hua; Wu, Qifeng (Frontiers in Public Health, 2022)
Background: The national essential public health service (NEPHS) has been in operation for more than a decade. Numerous studies examined the utilization of NEPHS by migrants and the factors that influence it, but few examined the effect of NEPHS awareness and utilization on the health of inhabitants, particularly migrants. The purpose of this study is to ascertain the level of awareness and utilization of NEPHS, as well as to examine their health-improving effects on migrants. Methods: Based on the data from the 2017 China Migrants Dynamic Survey, linear probability model, ordered logit model and the propensity score matching methods were employed to investigate impact of awareness and utilization of NEPHS on the health among Chinese migrants. Results: The findings indicated that migrants' awareness and utilization of NEPHS are still insufficient. After adjusting for other factors, the study discovered that increased awareness and use of NEPHS had a beneficial influence on migrants' self-rated health. Further heterogeneity analysis revealed significant disparities in the health consequences of NEPHS awareness and utilization across subgroups. The effect of increased awareness and usage of NEPHS on health is stronger for middle-aged and elderly people, women, and low-educated migrants with urban household registration. Conclusions: Given that migrants' NEPHS utilization is still low and that NEPHS utilization has a positive effect on health, some targeted strategies, such as a variety of new media communication methods, health education related to occupational disease and tuberculosis prevention, and targeted NEPHS projects for specific groups, such as men, young and middle-aged groups, those with a high level of education, and rural migrants, should be conducted to improve the health of migrants.